Towards decision support-based integrated management planning of papyrus wetlands: a case study from Uganda - Zsuffa, I.; Dam, A.A. van; Kaggwa, R.C.; Namaalwa, S.; Mahieu, M.; Cools, J.; Johnston, Robyn M. (2013)
Management and decision making for wetlands need an integrated approach, in which all ecosystem services are identified, their importance are assessed and objectives are formulated about their desired outputs. This approach has been applied successfully in European wetlands with sufficient scientific data. The main objective of this study was to evaluate the application of this approach in the context of a data-poor, multi-use African wetland. The Namatala wetland in Uganda, a wetland under intense pressure from wastewater discharge, conversion to agriculture and vegetation harvesting, was used as a case study. After characterisation of the wetland ecosystem and stakeholder analysis, three management options, subdivided into 13 sub-options, were identified for the wetland. These options were combined into six management solutions. A set of 15 indicators, subdivided into five categories (livelihood; human health; ecology; costs; risk of failure), were identified to assess the performance of these management solutions. Stakeholders' preferences were taken into consideration by means of weights attached to the indicators, and a best-compromise solution was derived which consisted of a combination of sustainable agriculture in the upper Namatala wetland, papyrus buffer strips along the Namatala river channel, sustainable land use (vegetation harvesting, fishing) in lower Namatala wetland, and papyrus buffer zones at the waste-water discharge points. Despite differences of opinion among stakeholder groups about the relative importance of the indicators, the same compromise solution resulted for all stakeholders. It was concluded that this systematic approach and the stakeholder dialogue about the management options were beneficial to the management process, although the approach would benefit from more and better data about the wetland system and from model-derived predictions.